REKONTRUKSI MAQASID SYARIAH DALAM PENGELOLAAN PERTAMBANGAN UNTUK MEWUJUDKAN WELFARE VILLAGE DI INDONESIA - Muh Alghifari; Muhammad Afdal Amirullah; Kurniati (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2026)
This study aims to analyze mining management through the reconstruction of maqasid sharia in order to realize sustainable mining governance and formulate a welfare village implementation model as a solution to the negative impacts of mining in Indonesia. The research method used is library research with a normative juridical approach and sharia theology, analyzing laws and regulations, maqasid sharia literature, mining journals, and government data related to mining. The results of the study indicate that current Indonesian mining management causes more environmental damage, social conflict, and economic inequality than benefits, with regulations that tend to benefit certain interests and ignore the people's maslahah. The reconstruction of maqasid sharia in the mining context includes expanding the classical meaning into four principles: hifz al-mal (distributive justice of mining results), hifz al-bi'ah (environmentally friendly mining), hifz al-'umran (village sustainable development), and hifz al-nafs wa al-sihhah (public health protection). The study's conclusion proposes a welfare village model as an implementation of the reconstruction of the maqasid sharia (Islamic principles) that integrates economic, social, and environmental values ​​through CSR-Maqasidiyyah instruments, local sharia institutions, and maqasid-based audits. This model shifts the paradigm of mere extraction to the development of sustainable collective benefits, placing the community as the primary subject of welfare while maintaining a balance between economic, humanitarian, and ecological interests.